Rotavirus Reverse Genetics Systems and Oral Vaccine Delivery Vectors for Mucosal Vaccination - Jun Wang; Songkang Qin; Kuanhao Li; Xin Yin; Dongbo Sun; Jitao Chang (Microorganisms)
Mucosal immunization represents a promising strategy for preventing enteric infections. Rotavirus (RV), a leading gastrointestinal pathogen distinguished by its remarkable stability and segmented double-stranded RNA genome, has been engineered into a versatile oral vaccine vector through advanced reverse genetics systems. The clinical efficacy of live-attenuated RV vaccines highlights their unique capacity to concurrently induce mucosal IgA responses and systemic neutralizing antibodies, positioning them as a multiple action vector for multiple immune protection. In this review, we summarize the RV colonization of the intestine and stimulation of intestinal immunity, as well as recent advancements in RV reverse genetics, and focus on their application in the rational design of a multivalent mucosal vaccine vector targeting enteric pathogens considering the advantages and challenges of RV as a vector. We further propose molecular strategies to overcome genetic instability in recombinant RV vectors, including the codon optimization of heterologous inserts. These insights provide a theoretical foundation for developing next-generation mucosal immunization platforms with enhanced safety, stability, and cross-protective efficacy.